Dance Extracurricular Learning Process for Character Building of Students at MTs Negeri 2 Lahat - Wilianah, Wilianah; NAD, Nugroho; Putra, Rio Eka (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to find out the character values of students through extracurricular dance activities at MTS Negeri 2 Lahat. The benefits of this research are theoretically, practically, for students and for the school. This research method uses a qualitative method, namely describing the character values of the students themselves. The data source for this research was obtained from trainers and MTS Negeri 2 Lahat students who took part in extracurricular activities, numbering approximately 18 people. The data collection techniques used are observation, interviews and documentation. The results of this research show that the character values of students who take part in dance extracurricular activities are quite good, which can be seen from the results of the evaluation of activities in the dance extracurricular learning process at MTS Negeri 2 Lahat.